2013
DOI: 10.1177/0021998313501922
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of circular composite patch reinforcement on damaged carbon fiber reinforced polymer laminate involving both mechanics-based and genetic algorithm in conjunction with 3D finite element analysis

Abstract: Composites are significantly used in aerospace, automotive and civil structures due to their high specific strength, high stiffness, corrosion resistant and longer fatigue life. During service life, composite structures are susceptible to damage, which reduces their structural integrity. For extending its service life, the damage needs to be repaired. In case of low velocity impact damage adhesively bonded patch repair is found to be effective in extending the service life of damaged parts. The repair performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The use of CFRP patches is an efficient and economic method for structural reinforcement. In addition to their excellent mechanical properties (e. g., high strength and stiffness), CFRP patches share multiple physical and chemical advantages (e. g., they are light weight, have great formability, and superior corrosion resistance); therefore, they are widely used in engineering fields, such as aerospace, automotive, and civil structures [22–28].…”
Section: Discussionmentioning
confidence: 99%
“…The use of CFRP patches is an efficient and economic method for structural reinforcement. In addition to their excellent mechanical properties (e. g., high strength and stiffness), CFRP patches share multiple physical and chemical advantages (e. g., they are light weight, have great formability, and superior corrosion resistance); therefore, they are widely used in engineering fields, such as aerospace, automotive, and civil structures [22–28].…”
Section: Discussionmentioning
confidence: 99%
“…Around the circular hole there are 15360 elements (96 circumferential; 40 radial; 4 thickness). The meshing surrounding the hole is chosen based on mesh convergence study [34,35]. Every layer is meshed with one element in thickness direction for both patch and panel.…”
Section: Finite Element Modeling and Analysismentioning
confidence: 99%
“…[ 19 ] Furthermore, the stresses produced in the repaired zone are also dependent on the adhesive and the patch thickness. [ 21 ] C. Soutis and F. Hu [ 22 ] reported that the patches with the edges tapered from inside result in localized thickening of the adhesive near the patch edges, leading to lower stress concentration in the adhesive layer. The stacking sequence of the parent laminate also influences the behavior of repaired system.…”
Section: Introductionmentioning
confidence: 99%